2010
DOI: 10.1111/j.1539-6924.2010.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Differences in Risk Perceptions of Disasters

Abstract: Public risk perceptions of mass disasters carry considerable influences, both psychologically and economically, despite their oft-times imprecise nature. Prior research has identified the presence of an optimistic bias that affects risk perception, but there is a dearth of literature examining how these perceptions differ among cultures-particularly with regard to mass disasters. The present study explores differences among Japanese, Argentinean, and North American mental health workers in their rates of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(102 citation statements)
references
References 31 publications
5
94
0
3
Order By: Relevance
“…In this case, students exhibiting optimistic bias took fewer precautions against swine flu than did students who believed they were vulnerable. Other research findings confirm optimistic bias regarding a wide range of health risks, including sun tanning and cancer risks (Craciun, Shuz, Lippke, & Schwarzer, 2010), risky driving (Dean, 2010;Morisset, Terrade, & Somat, 2010), smoking (Burrows & Carlisle, 2010;Wagener, Gregor, Busch, McQuaid, & Borrelli, 2010), and natural disasters (Gierlach, Belsher, & Beutler, 2010;Weinstein, Lyon, Rothman, & Cuite, 2000).…”
Section: According To the Rape Abuse And Incest National Networkmentioning
confidence: 85%
“…In this case, students exhibiting optimistic bias took fewer precautions against swine flu than did students who believed they were vulnerable. Other research findings confirm optimistic bias regarding a wide range of health risks, including sun tanning and cancer risks (Craciun, Shuz, Lippke, & Schwarzer, 2010), risky driving (Dean, 2010;Morisset, Terrade, & Somat, 2010), smoking (Burrows & Carlisle, 2010;Wagener, Gregor, Busch, McQuaid, & Borrelli, 2010), and natural disasters (Gierlach, Belsher, & Beutler, 2010;Weinstein, Lyon, Rothman, & Cuite, 2000).…”
Section: According To the Rape Abuse And Incest National Networkmentioning
confidence: 85%
“…Perceived work safety is a highly subjective construct (Gierlach, Belsher & Beutler, 2010), and differences in safety-specific knowledge may explain variations in this variable. So can a person's involvement in the day-to-day operations of a business.…”
Section: Work Safety Management and Perceived Work Safetymentioning
confidence: 99%
“…The notion of culturally driven risk perception having influence on the application of the SRI is not implausible when cultural theory is considered. In order to gain a better understanding, Gierlach et al (2010) investigated this phenomenon with interesting results. They found that risk perception across cultures has little to do with exposure to a disaster and more to do with an optimistic bias or "not in my backyard" mentality generated by social construct (Emerging Health Threats Forum, 2008).…”
Section: Risk Perception In Austriamentioning
confidence: 99%